Economic assessment of intellectual and innovative technologies in the context of sustainable development - Prokhorova, Viktoriia; Mrykhina, Oleksandra; Koleshchuk, Orest; Babichev, Anatoliy; Dudnieva, Iuliia; Slastianykova, Krystyna (Technology audit and production reserves, 2025)
The object of research is the processes of economic evaluation of intellectual and innovative technologies in the context of sustainable development. The problem of economic evaluation of such technologies is caused by the insufficiency of the current methodological framework, which is substantiated with the use of the VosViewer bibliometric toolkit. The paper identifies the need to implement intellectual and innovative technologies aimed at achieving the goals of sustainable development, as well as their projects, using the example of the Golden Ducat Jewellery Company (Ukraine). To substantiate the choice of intellectual and innovative technologies, a methodological approach has been developed based on a system of parameters for expert assessment of the level of intellectualisation of technologies (autonomy, adaptability, machine learning, interactivity, integration). The author’s approach is proposed to be implemented with the help of a mathematical model based on matrices, using the methods of fuzzy set theory. The practical results of applying the model have shown that the most intellectualised technology is the interactive jewellery design studio, which corresponds to the system of parameters by 73.43 %. Other technologies have lower degrees of compliance: 3D visualisation and virtual fitting – 47.16 %, integration of online platforms – 40.50 %, interactive learning services – 34.09 %, and eco-design of products – 23.35 %. The article compares the parameters of intellectualisation of technologies with the expected economic performance of a company due to the implementation of these technologies. It is found that the parameters of ‘autonomy’ and ‘machine learning’ have the greatest impact on the level of intellectualisation. Accordingly, the most effective technologies are an interactive jewellery design studio (ROI – 64.19 %, payback period – 7.3 months) and eco-design of products (ROI – 69.47 %, payback period – 7.2 months). It is found that for a reasonable choice of intellectual and innovative technologies it is important to take into account factors such as market demand, long-term trends and business specifics.